2015
DOI: 10.1016/j.bbadis.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of β-amyloid and ceramide-induced insulin resistance on mitochondrial metabolism in neuronal cells

Abstract: A large body of evidence support major roles of mitochondrial dysfunction and insulin action in the Alzheimer's disease (AD) brain. However, interaction between cellular expression of β-amyloid (Aβ) and insulin resistance on mitochondrial metabolism has not been explored in neuronal cells. We investigated the additive and synergistic effects of intracellular Aβ42 and ceramide-induced insulin resistance on mitochondrial metabolism in SH-SY5Y and Neuro-2a cells. In our model, mitochondria take-up Aβ42 expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 120 publications
(170 reference statements)
0
15
0
Order By: Relevance
“…These previous studies and current data led us to hypothesize that improved mitochondrial function and inflammatory resilience of LBP KD cells could be attributed to decreased inflammatory lipid mediators that induced inflammation and NF‐κB pathway in adipocytes , such as ceramides and arachidonate‐containing glycerolipids, which were reduced in these cells. In fact, these lipid mediators also promoted mitochondrial dysfunction . Inflammation is a crucial pathophysiological underlying factor leading to adipose tissue dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies and current data led us to hypothesize that improved mitochondrial function and inflammatory resilience of LBP KD cells could be attributed to decreased inflammatory lipid mediators that induced inflammation and NF‐κB pathway in adipocytes , such as ceramides and arachidonate‐containing glycerolipids, which were reduced in these cells. In fact, these lipid mediators also promoted mitochondrial dysfunction . Inflammation is a crucial pathophysiological underlying factor leading to adipose tissue dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide has been shown to activate fission of mitochondria in various tissues and in a cellular model, acting through modulation of expression levels of BOK (Bcl-2-related ovarian killer protein) [ 251 ]. Ceramide inhibits Akt signaling (synergistically with intracellular amyloid β 42 (Aβ 42 )) and disturbs the fusion-fission regulation in neuronal cell lines through down-regulation of the fusion-promoting proteins mitofusin 1 and OPA1 (optic atrophy 1) [ 252 ] ( Fig. 4 ) .…”
Section: Bioactive Sphingolipids In Agingmentioning
confidence: 99%
“…4 ) . Ceramide also reduced the levels of the fission regulator dynamin-related protein 1, although in muscle cells its seemed to exert opposite effect [ 252 , 253 ]. Likewise, loss of the ceramide transfer protein CERT results in disturbed transport of ceramides from endoplasmic reticulum to Golgi apparatus, hexosylceramide accumulation in mitochondria, and lower frequency of both fusion and fission [ 254 ].…”
Section: Bioactive Sphingolipids In Agingmentioning
confidence: 99%
“…Amyloid beta is thought to interact with several proteins amongst others some mitochondrial proteins, resulting in an increase in oxidative stress [15] which in turn could increase Aβ levels [16]. Regarding the mitochondrial respiratory system, in vitro studies on isolated mitochondria showed the reduced activity of pyruvate dehydrogenase and Cytochrome c Oxidase after Aβ treatment [17, 18]. Likewise, Aβ treatment of brain homogenate impaired mitochondrial oxygen consumption as well as mitochondrial membrane potential [19].…”
Section: Introductionmentioning
confidence: 99%